Groundbreaking scientific experiments, inventions, and discoveries of the Middle Ages and the Renaissance - Krebs, Robert E. (Greenwood, 2004)
The Middle Ages and the Renaissance were a period of scientific and literary reawakening. This reference work describes more than 75 experiments, inventions, and discoveries of the period, as well as the scientists, physicians, and scholars responsible for them. Individuals such as Leonardo da Vinci, Marco Polo, and Galileo are included, along with entries on reconstructive surgery, Stonehenge, eyeglasses, the microscope, and the discovery of smallpox. The history and development of nearly 75 discoveries, inventions, and experiments of the period are traced.
Keywords: Geschichte 500-1600; Experimenten; Ontdekkingen; Sciences de la Renaissance; Sciences médiévales; Technologie - Histoire; Uitvindingen; Geschichte; Science, Medieval; Science, Renaissance; Technology -- History; Naturwissenschaften; Experiment; Entdeckung